Influence of plant growth promoting rhizobacteria And organic manures on yield of okra (abelmoschus esculentus (l.) Moench) - Dhiman, Shivali; Kumari, Santosh; Dogra, Balbir Singh; Sohi, Anuj; Chaudhary , Parveen; Saini, Anubha (Bangladesh Journal of Botany, 2024)
The investigation revealed that different growth and yield parameters viz., minimum days to first flowering, earliest first flowering node, minimum days to first fruit harvest and maximum plant height, average fruit weight, fruit length, fruit breadth, fruit yield per plant, fruit yield per plot and harvest duration were recorded in treatment combination of FYM + Vermicompost + Jeevamrit + Pseudomonas fluorescens. Therefore, supply of plant nutrients through organic sources like vermicompost, FYM, jeevamrit and Pseudomonas fluorescens enhance plant growth and development, increase soil nutrient status and maintain sustainable crop production. Bangladesh J. Bot. 53(4): 1021-1025, 2024 (December)